(−)‐Epicatechin rescues the As2O3‐induced HERG K+ channel deficiency possibly through upregulating transcription factor SP1 expression. Issue 11 (2nd August 2017) - Dong, Zengxiang; Shi, Yuanqi; Feng, Lifang; Shen, Zhaoqian; Fang, Li; Zheng, Sijia; Hai, Xin; Li, Baoxin
Abstract: (−)‐Epicatechin (EPI) has beneficial effects on the cardiovascular disease. The human ether‐a‐go‐go‐related gene (HERG) potassium channel is crucial for repolarization of cardiac action potential. Dysfunction of the HERG channel can cause long QT syndrome type 2 (LQT2). Arsenic trioxide (As2 O3 ) has shown efficacy in the treatment of acute promyelocytic leukemia. However, As2 O3 can induce the deficiency of HERG channel and cause LQT2. In this study, we examined whether EPI could rescue the As2 O3 ‐induced HERG channel deficiency. We found that 3 μM EPI obviously increased protein expression and current of HERG channel. EPI was able to recover the protein expression and current of HERG channel disrupted by As2 O3 . EPI was able to increase the expression of SP1 protein and recover the expression of SP1 protein disrupted by As2 O3 . In addition, EPI significantly shortened action potential duration prolonged by As2 O3 . Our data suggest that EPI rescues As2 O3 ‐induced HERG channel deficiency through upregulating SP1 expression.